The Information Value of Stock Lending Fees: Are Lenders Price Takers? - Duong, Truong X; Huszár, Zsuzsa R; Tan, Ruth S K; Zhang, Weina (Review of Finance, 2017)
We find that higher stock lending fees predict significantly lower future returns after controlling for shorting demand for US stocks during the period 2007–10. These results suggest that active institutional investors on the supply side play an important role in the return predictability of fees and they not only respond to demand but also price in additional information around earnings news announcements. Overall, we find evidence that stock lenders are informed and, together with short sellers, contribute to the price discovery process.